High opsonic phagocytosis activity and growth inhibition of merozoites are associated with RON4 antibody levels and protect against febrile malaria in Ghanaian children - Kyei-Baafour, Eric; Kusi, Kwadwo Asamoah; Arthur, Fareed K.N.; Tiendrebeogo, Regis W.; Owusu-Yeboa, Eunice; Singh, Susheel K.; Friedrich, Sarah; Gerds, Thomas A.; Dodoo, Daniel; Theisen, Michael; Adu, Bright (Frontiers in Immunology, 2023)
Naturally acquired immunity to malaria may involve different immune mechanisms working in concert, however, their respective contributions and potential antigenic targets have not been clearly established. Here, we assessed the roles of opsonic phagocytosis and antibody-mediated merozoite growth inhibition in Plasmodium falciparum (P. falciparum) infection outcomes in Ghanaian children. The levels of merozoite opsonic phagocytosis, growth inhibition activities and six P. falciparum antigen-specific IgG of plasma samples from children (n=238, aged 0.5 to 13 years) were measured at baseline prior to the malaria seasons in southern Ghana. The children were then actively and passively followed up for febrile malaria and asymptomatic P. falciparum infection detection in a 50-week longitudinal cohort. P. falciparum infection outcome was modelled as a function of the measured immune parameters while accounting for important demographic factors. High plasma activity of opsonic phagocytosis [adjusted odds ratio (aOR)= 0.16; 95%CI= 0.05 - 0.50, p = 0.002], and growth inhibition (aOR=0.15; 95% CI = 0.04-0.47; p = 0.001) were individually associated with protection against febrile malaria. IgG antibodies against MSPDBL1 correlated with opsonic phagocytosis (OP) while IgG against PfRh2a correlated with growth inhibition. Notably, IgG antibodies against RON4 correlated with both assays. Opsonic phagocytosis and growth inhibition are protective immune mechanisms against malaria that may be acting independently to confer overall protection as these two assays showed no evidence of correlation (β= 0.13; 95% CI= -0.04-0.30; p=0.14). Vaccines incorporating RON4 may benefit from both immune mechanisms.